On Skew Circulant Type Matrices Involving Any Continuous Fibonacci Numbers - Zhaolin Jiang; Jinjiang Yao; Fuliang Lu (Abstract and Applied Analysis)
Circulant and skew circulant matrices have become an important tool in networks engineering. In this paper, we consider skew circulant type matrices with any continuous Fibonacci numbers. We discuss the invertibility of the skew circulant type matrices and present explicit determinants and inverse matrices of them by constructing the transformation matrices. Furthermore, the maximum column sum matrix norm, the spectral norm, the Euclidean (or Frobenius) norm, and the maximum row sum matrix norm and bounds for the spread of these matrices are given, respectively.